Nýlistasafnid. (Reykjavik : The Living Art Museum, 1994)
Gisladóttir, Elsa Dóróthea ; Hjartardóttir, Gudrún ; Straumland, Gunnar J. ; Hjaltalín Eyjólfsson, Helgi ; Bergmann Kjartansson, Jón ; Örn Fridriksson, Pétur ; Hoekstra, Rob ; Porbergsdóttir, Sólveig
Nýlistasafnid / The Living Art Museum, 23. Nov. - 11. Des. 1994
boek